Atrial septal defect occlusion by a catheter during reperfusion of homograft in a case of living donor liver transplantation. (8th August 2021) - Baba, Shiro; Hirata, Takuya; Okajima, Hideaki
Abstract: Liver transplantation for patients with atrial septal defect and pulmonary artery stenosis, causing high right atrium pressure, raises concerns about embolism in systemic vessels during reperfusion of the donor liver graft. Temporal atrial septal defect occlusion by a catheter is a simple and easy method of preventing the complication.